2022
DOI: 10.3390/biomedicines10123294
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Use of Empagliflozin—A Comprehensive Review

Abstract: Empagliflozin is a relatively new drug that, as an inhibitor of the sodium–glucose cotransporter 2 (SGLT2), causes increased urinary glucose excretion and thus contributes to improved glycemic control, better glucose metabolism, reduced glucotoxicity and insulin resistance. Although its original use was to induce a hypoglycemic effect in patients with type 2 diabetes mellitus (T2DM), empagliflozin has also shown a number of other beneficial effects by demonstrating a nephroprotective effect, and it has proven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…Subsequent studies confirmed that the glucosuric effects of empagliflozin resulted in a decrease of plasma glucose levels (38)(39)(40)(41), glycemic spikes and HbA1c levels (42). However, empagliflozin has pleiotropic effects, such as reducing insulin levels, insulin resistance, glucotoxicity and lipotoxicity, and increasing glucagon secretion and ketone bodies production (42,43). Furthermore, empagliflozin improves redox state and oxidative stress, inhibiting reactive oxygen species (ROS) production, reducing the activity of pro-oxidant agents, and improving mitochondrial function (44).…”
Section: Evidences From Diabetes 431 Metabolic Effectsmentioning
confidence: 86%
See 3 more Smart Citations
“…Subsequent studies confirmed that the glucosuric effects of empagliflozin resulted in a decrease of plasma glucose levels (38)(39)(40)(41), glycemic spikes and HbA1c levels (42). However, empagliflozin has pleiotropic effects, such as reducing insulin levels, insulin resistance, glucotoxicity and lipotoxicity, and increasing glucagon secretion and ketone bodies production (42,43). Furthermore, empagliflozin improves redox state and oxidative stress, inhibiting reactive oxygen species (ROS) production, reducing the activity of pro-oxidant agents, and improving mitochondrial function (44).…”
Section: Evidences From Diabetes 431 Metabolic Effectsmentioning
confidence: 86%
“…Chronic dosing shifted the substrate utilization from carbohydrates to lipids (37). Subsequent studies confirmed that the glucosuric effects of empagliflozin resulted in a decrease of plasma glucose levels (38)(39)(40)(41), glycemic spikes and HbA1c levels (42). However, empagliflozin has pleiotropic effects, such as reducing insulin levels, insulin resistance, glucotoxicity and lipotoxicity, and increasing glucagon secretion and ketone bodies production (42,43).…”
Section: Evidences From Diabetes 431 Metabolic Effectsmentioning
confidence: 98%
See 2 more Smart Citations
“…Chemie thalene-containing γ-lactone 29 was afforded in moderate 64 % yield with 37 % ee. Furthermore, involving a scaffold of bioactive compounds provided empagliflozin [14] derivative 30 in 74 % yield with 16 : 1 dr and a canagliflozin [15] derivative 31 in 78 % yield with 83 % ee. Last but not least, non-activated olefins devoid of an aryl or alkynyl substituent were investigated.…”
Section: Methodsmentioning
confidence: 99%